1956
DOI: 10.5962/bhl.title.6435
|View full text |Cite
|
Sign up to set email alerts
|

The biology of senescence

Abstract: The Measurement of senescence 1 24 33 Drosophila subobscura-hybrid vigour and longevity. Survival curves for the inbred lines B and K, and for the reciprocal hybrids between them 128 34 Survivorship curves for 82 males and 45 females of the black widow spider Latrodectes mactans 131 xii Illustrations 35 Survivorship, death and death-rate curves for the black widow. 36 Survivorship curves for male and female Tribolium madens 131 37 Effect of restricted food upon the longevity of Daphnia longispina 38 Effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
203
1
17

Year Published

1982
1982
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(225 citation statements)
references
References 195 publications
(290 reference statements)
4
203
1
17
Order By: Relevance
“…Stocks were maintained separately for three or four generations at a density of more than 50 pairs per pint bottle and renewed at 10-14 days. To promote as extensive a variability as possible and following the methods of Lints and his coworkers (1974;1979), stocks were crossed such that each contributed equally in the creation of a four-way hybrid population. To permit the expression and equilibration of recombinants before selection, replicate lines of the hybrid population were then reproduced at 7-10 days for eight consecutive generations before selection was initiated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stocks were maintained separately for three or four generations at a density of more than 50 pairs per pint bottle and renewed at 10-14 days. To promote as extensive a variability as possible and following the methods of Lints and his coworkers (1974;1979), stocks were crossed such that each contributed equally in the creation of a four-way hybrid population. To permit the expression and equilibration of recombinants before selection, replicate lines of the hybrid population were then reproduced at 7-10 days for eight consecutive generations before selection was initiated.…”
Section: Methodsmentioning
confidence: 99%
“…While early experimental studies by Clark and Maynard Smith (1955) found heterosis in the longevity of outcrossed populations, other studies by Comfort (1979) have described the patterns that emerge from the comparison of life span in different organisms. Collectively, the many such life historical and genetic studies do generally establish the existence of the genetic control of longevity, but they provide little more than implication toward the fundamental question of evolutionary interest "How do long and short life spans evolve?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this time, various general theories as to the nature of the ageing process were put forward (for reviews see Medawar 1946 andComfort 1979), but these placed little emphasis on the influence of natural selection. Prominent among them were (i) the "optimistic studies" of Metchnikoff (1907) who sought to relate ageing to the influence of invading poisons, supposed to originate mainly from microbes in the gut; (ii) the view that ageing is related directly to growth, either through the differentiation of cells into terminal forms incapable of growth or repair (Minor 1907), or as a by-product of the continued action of the mechanism to limit growth as soon as specific size is reached (Bidder 1932)2; (iii) the hypothesis of Child (1915), based largely on extensive experimental research with planaria (Child 1911), that ageing is associated with a decrease in the rate of metabolism which results in the accumulation within the cell of "structural obstacles to metabolism" such as inactive wastes; and (iv) the "rate of living" theory of Pearl (1928), who proposed that the duration of life varies in inverse proportion to the rate of energy expenditure as a result of a finite total amount of "vitality" being used up.…”
Section: Theories On Evolution Of Ageing After Weismannmentioning
confidence: 99%
“…Comfort 1979): "Death takes place because a worn-out tissue cannot for ever renew itself''. When read in context (see Section 2), it is clear that Weismann did not intend this sentence to have the circular meaning which seems so obvious when it is read by itself.…”
Section: Weismann Reappraisedmentioning
confidence: 99%